CO2 reduction methods and evaluation of proposed energy efficiency improvements in Poland's large industrial plant. (1st July 2020) - Broniszewski, Mariusz; Werle, Sebastian
Abstract: Under the Kyoto protocol, many countries and international communities in general have ambitious targets for the reduction of greenhouse gas (mainly CO2 ) emissions and global warming. Globally, industrial primary energy use and conversion for electricity and heat are responsible for 46% of greenhouse gas emissions. In Europe, the introduction of the Energy Efficiency Directive in 2012 has led to an increase in the number of Energy Efficiency Obligations - EEOs (also known as White Certificates or energy efficiency resource standards across Europe). 12 EU Member States (Austria, Bulgaria, Denmark, France, Ireland, Italy, Luxembourg, Malta, Poland, Slovenia, Spain, UK) have active EEOs with another four due to start shortly (Croatia, Greece, Latvia and the Netherlands) considering their introduction. Due to this fact, in Poland, pro-efficiency investments are gaining in popularity. Industrial plant Bulten Poland S.A. dealing the production of fasteners for the automotive industry has a heat treatment department, which is the most energy-intensive part in the manufacture of screw products. It results in significant carbon footprint (total CO2 emission from gas usage at the heat treatment department is at the level of 3, 885 Mg/year). For this reason, to increase energy efficiency and simultaneously reduce CO2 emission, waste heat recovery has been introduced on the Aichelin hardening line. The heat recovery has been located on the oil bath and at the exhaust pipe from the gas burners. The recovered waste heat is captured by the buffer in the form of a water tank. The water is injected into the central heating system and used in the heating season to maintain appropriate temperatures in the halls and offices. Furthermore, the possibility of installing cogeneration unit has been investigated as a way to minimize carbon footprint of the production. The work presents an analysis of improving the energy efficiency and reduce of CO2 emission by implementing solutions such as: heat recovery and use a cogeneration unit. Estimated CO2 savings are at the level of 1, 350 Mg/year which gives about 35% of total emission. Highlights: Waste heat recovery and cogeneration provides an attractive solutions within increasing energy efficiency and reduce of CO2 emissions. Feasibility evaluation of proposals were presented. Simple payback time calculations were included. Potential of CO2 reduction was shown. New law regulations within government funding for cogeneration were mentioned.